Is human capital losing from outsourcing? : Evidence for Austria and Poland - Andzelika Lorentowicz; Dalia Marin; Alexander Raubold (Center for Economic Studies and ifo Institute (CESifo), 2005)
Feenstra and Hanson (1997) have argued in the context of the North American Free Trade Agreement that US outsourcing to Mexico leads to an increase in the skill premium in both the US and Mexico. In this paper we show on the example of Austria and Poland that with the new international division of labour emerging in Europe Austria, the high income country, is specializing in the low skill intensive part of the value chain and Poland, the low income country, is specializing in the high skill part. As a result, skilled workers in Austria are losing from outsourcing, while gaining in Poland. In Austria, relative wages for human capital declined by 2 percent during 1995-2002 and increased by 41 percent during 1994-2002 in Poland. In both countries outsourcing contributes roughly 35 percent to these changes in the relative wages for skilled workers. Furthermore, we show that Austria's R&D policy has contributed to an increase in the skill premium there
Keywords: J31; F23; F21; P45; 330; Direktinvestition; Internationale Arbeitsteilung; Humankapital; Outsourcing; Multinationales Unternehmen; Lohnstruktur; Vergleich; Österreich; Polen